Views of first grade teachers on soundbased sentence method and writing types - Turan, Mehmet (My University, 2010)
Present study was performed to determine views of first grade teachers in primary schools on sound-based sentence method, italic handwriting and other writing types. Research was carried out on total 102 first grade teachers who worked in the center of Elazi{dotless}?. Research is in descriptive survey model. The data were collected through the questionnaire developed by the researcher. From obtained data analysis, frequency and percentage, mean, independent samples t test and chi-square test were used. As a result of the research, it was determined that 95 % of the first grade students, who were taught with sound-based sentence method, acquired the skills of freely reading-writing due on the end of March. Also, it was found that first grade students were able to achieve syllable very comfortable and they were able to write fast italic handwriting in the sound-based sentence method. Parents viewed sound-based sentence method and italic handwriting as partially positive. However, it was determined that parents did not have sufficient information about this method and writing type. Also, it was identified most first grade students had difficulty when writing "f","s", "r", "ş", "k", "b", "h" and "z" letters. Furthermore, most students confused when writing b-d", "r-n","n-m" ve "c-ç" letters and it was determined that they mostly confused when "b-d", "?", "h", "g", "f", "v", "p", "c" and "r". sounds are called.
Birinci sinif ö?retmenlerinin ses temelli cümle yöntemi ve yazi türlerine ilişkin görüşleri
Keywords: Italic-hand writing; Sound-based sentence method; Writing types